Brain Abnormalities in Neuromyelitis Optica Spectrum Disorder. (3rd December 2012) - Kim, Woojun; Kim, Su-Hyun; Huh, So-Young; Kim, Ho Jin
Abstract : Neuromyelitis optica (NMO) is an idiopathic inflammatory syndrome of the central nervous system that is characterized by severe attacks of optic neuritis (ON) and myelitis. Until recently, NMO was considered a disease without brain involvement. However, since the discovery of NMO-IgG/antiaqaporin-4 antibody, the concept of NMO was broadened to NMO spectrum disorder (NMOSD), and brain lesions are commonly recognized. Furthermore, some patients present with brain symptoms as their first manifestation and develop recurrent brain symptoms without ON or myelitis. Brain lesions with characteristic locations and configurations can be helpful in the diagnosis of NMOSD. Due to the growing recognition of brain abnormalities in NMOSD, these have been included in the NMO and NMOSD diagnostic criteria or guidelines. Recent technical developments such as diffusion tensor imaging, MR spectroscopy, and voxel-based morphometry reveal new findings related to brain abnormalities in NMOSD that were not identified using conventional MRI. This paper focuses on the incidence and characteristics of the brain lesions found in NMOSD and the symptoms that they cause. Recent studies using advanced imaging techniques are also introduced.